2021
DOI: 10.1002/ijgo.13676
|View full text |Cite
|
Sign up to set email alerts
|

Stay Home, Stay Connected: A virtual model for enhanced prenatal support during the COVID‐19 pandemic and beyond

Abstract: Synopsis Virtual prenatal support groups addressed heightened mental health, psychosocial support, and anticipatory guidance needs in pregnant patients during the COVID‐19 pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…While hospital-based obstetric care remained an essential service during the COVID-19 pandemic, outpatient prenatal care experienced substantial disruptions, and much routine care was done virtually. 41 , 42 It is possible that these disruptions and limitations in monitoring with telehealth may have contributed to the slight worsening of pregnancy-related complications. Additionally, increased rates of hypertensive disorders may be due to heightened stress provoked by the pandemic, or reluctance to engage in for prenatal care due to concerns about COVID-19 exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While hospital-based obstetric care remained an essential service during the COVID-19 pandemic, outpatient prenatal care experienced substantial disruptions, and much routine care was done virtually. 41 , 42 It is possible that these disruptions and limitations in monitoring with telehealth may have contributed to the slight worsening of pregnancy-related complications. Additionally, increased rates of hypertensive disorders may be due to heightened stress provoked by the pandemic, or reluctance to engage in for prenatal care due to concerns about COVID-19 exposure.…”
Section: Discussionmentioning
confidence: 99%
“…While SARS-CoV-2 was low in our sample, our work extends these findings to demonstrate the associations of the overall disruptions of the COVID-19 pandemic with the health of pregnant people. While hospital-based obstetric care remained an essential service during the COVID-19 pandemic, outpatient prenatal care experienced substantial disruptions, and much routine care was done virtually . It is possible that these disruptions and limitations in monitoring with telehealth may have contributed to the slight worsening of pregnancy-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…] 2021 Israel 421 N/A 102 Liu CH [ 109. ] 2021 US 628 p < 0.01 103 Ramirez Biermann C [ 110. ] 2021 US 162 N/A 104 Palalioglu RM [ 111.…”
Section: Resultsmentioning
confidence: 99%
“…] Wuhan 817 2021 Anxiety SAS Mirzaei N [ 104. ] Iran 200 2021 Anxiety,Depression HADS-A, HADS-D Ramirez Biermann C [ 110. ] US 162 2021 Anxiety,Depression self-designed questionnaire Palalioglu RM [ 111.…”
Section: Resultsmentioning
confidence: 99%
“…A cross-sectional study conducted during the stay-at-home order found that unhealthy lifestyles involving smoking and drinking habits and being a female were important risk factors for depressive symptoms, whereas having exercise habits and someone to consult about worries were protective factors (24) . A short report suggested that staying connected was important even when staying at home (25) . Pregnant women with COVID-19 reportedly had a disproportionately poor socioeconomic status, regardless of the economic status of the country (26) .…”
Section: Impact Of Disasters On Pregnant Womenmentioning
confidence: 99%